2015
DOI: 10.1021/acsami.5b00149
|View full text |Cite
|
Sign up to set email alerts
|

Improved Hole-Transporting Property via HAT-CN for Perovskite Solar Cells without Lithium Salts

Abstract: A nonadditive hole-transporting material (HTM) of a triphenylamine derivative of N,N'-di(3-methylphenyl)-N,N'-diphenyl-4,4'-diaminobiphenyl (TPD) is used for the organic-inorganic hybrid perovskite solar cells. The power conversion efficiency (PCE) can be significantly enhanced by inserting a thin layer of 1,4,5,8,9,11-hexaazatriphenylenehexacarbonitrile (HAT-CN) without adding an ion additive because the hole-transporting properties improve. The short-circuit current density (J(sc)) increases from 8.5 to 13.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Without using any dopants, PCEs up to 12% have been achieved for perovskite devices with mesoscopic architecture. In a study, Ma et al have used N,N′‐di(3‐methylphenyl)‐N,N′diphenyl‐4,4′‐diaminobiphenyl (TPD) ( 47 ) as the HTM of PSC and without using any dopants, a low efficiency of 3.2% has been obtained . However, employing 1,4,5,8,9,11‐hexaazatriphenylenehexacarbonitrile (HAT‐CN), as a buffer layer between HTM and Au electrode, with the optimum thickness of 3 nm, has improved the PCE up to 7.1%.…”
Section: Dopant‐free Hole Transporting Materials For Pscsmentioning
confidence: 99%
“…Without using any dopants, PCEs up to 12% have been achieved for perovskite devices with mesoscopic architecture. In a study, Ma et al have used N,N′‐di(3‐methylphenyl)‐N,N′diphenyl‐4,4′‐diaminobiphenyl (TPD) ( 47 ) as the HTM of PSC and without using any dopants, a low efficiency of 3.2% has been obtained . However, employing 1,4,5,8,9,11‐hexaazatriphenylenehexacarbonitrile (HAT‐CN), as a buffer layer between HTM and Au electrode, with the optimum thickness of 3 nm, has improved the PCE up to 7.1%.…”
Section: Dopant‐free Hole Transporting Materials For Pscsmentioning
confidence: 99%
“…29 Removing the need for external dopants can also be achieved by synthesizing novel hole-transport materials which have tailored energy levels and inherently good charge transport characteristics and therefore do not require additional doping for efficient charge extraction. 22,24,25,27,30 Promising results were obtained by Kim et al, employing a newly synthesized polymer as hole-transporter which was shown to protect the perovskite absorber for 1400 h at 75% relative humidity in the dark and at room temperature ( Fig. 1(c)).…”
mentioning
confidence: 97%
“…[5][6][7] Metal-free HAT derivatives can display liquid crystal behaviour, 8 which, in tandem with their electron transport and semiconductor properties, 9 has introduced potential uses in organic electronics. [10][11][12][13][14][15] Electron-deficient HAT derivatives have also been used for anion recognition applications. 16 The ability of HAT-type ligands to bind up to three transition metal ions is of interest in the context of molecular magnetism.…”
mentioning
confidence: 99%